Kinerja Polisi Lalu Lintas Dalam Sosialisasi E-Tilang Di Kota Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study wad to find out how the performance of traffic police in the e-ticket socialization in the city of Makassar. This study  used  descriptive qualitative research. Data collection techniques used observation, interviews with the amount of information as many as 8 people. Data analysis techniques used  data reduction, data presentation and conclusion. The validity of the data used triangulation namely time triangulation, source triangulation and technical triangulation. The results of this study could be seen that the performance of traffic police in socializing e-ticketing in the city of Makassar, in making policies that set  narrowing the bureaucracy and accelerating the process of public service. The implementation of this e-ticketing policy had several agencies involved including, the police, courts, prosecutors and banks that had their respective roles in providing maximum services to the public in the management of e-ticketing. But in its implementation it was still constrained by existing human resources and was still classified as less competent in utilizing existing technology. Keywords: Police Performance, E-Ticket Socialization